Promoting Preschoolers' Emotional Competence Through Prosocial TV and Mobile App Use. Issue 1 (2nd January 2019) - Rasmussen, Eric E.; Strouse, Gabrielle A.; Colwell, Malinda J.; Russo Johnson, Colleen; Holiday, Steven; Brady, Kristen; Flores, Israel; Troseth, Georgene; Wright, Holly D.; Densley, Rebecca L.; Norman, Mary S.
ABSTRACT: This study explored the relationship between preschoolers' exposure to Daniel Tiger's Neighborhood television programming and its accompanying mobile app and preschoolers' emotion knowledge and use of emotion regulation strategies. An experiment involving 121 parent-child dyads from 3 US metro areas found that children who played with the Daniel Tiger's Neighborhood app, and those who both played with the app and watched episodes of the program, employed the emotion regulation strategies taught by Daniel Tiger's Neighborhood media more frequently 1 month later than children in a control condition. Preschoolers (3- and 4-year-olds) also exhibited higher levels of emotion knowledge 1 month after playing with the app. In addition, watching Daniel Tiger's Neighborhood TV episodes in the home led to increases in parents' provision of active mediation. Implications for families, educators, and producers of educational media content are discussed.